2019
DOI: 10.1002/ese3.524
|View full text |Cite
|
Sign up to set email alerts
|

Local buckling evolution mechanism of a buried steel pipe under fault movements

Abstract: Pipe is the main transportation way for oil and natural gas. Fault movement mainly caused by earthquake, which will induce pipe bending, tension and compression. Then oil or gas leakage appear. Based on the moving mechanism of strike‐slip fault and reverse fault, a numerical simulation model was employed to study the buckling evolution mechanism of the buried steel pipe under fault movements. The evolution processes of buried pipe under the fault moving action were analyzed, and the effects of pipe internal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
(35 reference statements)
0
12
0
Order By: Relevance
“…The buckling moment Mc and buckling stress σc corresponding to the cylindrical shell can be obtained by Eqs. ( 6) and (7) [27]:…”
Section: Pipe Local Buckling Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The buckling moment Mc and buckling stress σc corresponding to the cylindrical shell can be obtained by Eqs. ( 6) and (7) [27]:…”
Section: Pipe Local Buckling Mechanismmentioning
confidence: 99%
“…The pipeline under the composed fault may be more dangerous and the pipe local buckling behavior (potential local buckling locations and the developing process) under single fault displacement may not accurately evaluate that under the composed fault. Besides, the local buckling of the pipeline as a cylindrical shell will experience an obvious stage feature under axial compression [7,20,21]. The clear developing process of the pipe local buckling is of great significance to the pipe safe operation and maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was concluded that cohesive soils, softer ground conditions, smaller diameter to thickness ratio, smaller pipe internal pressure and X80 steel material (compared with X65) result in a better deformation capacity of the buried pipeline. Similar FE models have been proposed and employed to describe mechanical behavior of steel pipelines crossing strike-slip faults taking boundary conditions into consideration [ 7 ], and mechanical behavior of steel pipelines crossing reverse faults [ 8 , 9 , 10 ] and oblique reverse faults [ 11 ]. In addition to the M-C model, the Drucker–Prager (D-P) model was, also, used to analyze mechanical response of steel pipe subjected to strike-slip fault movement with emphasis on the effects of fault modelling [ 12 ] and mechanical behavior of steel pipe under reverse fault displacement [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The microscopic parameters of the model are calibrated by triaxial tests [15]. Zhang et al use a numerical simulation model to study the bending evolution mechanism of buried steel pipe under fault movement and discuss the influence of internal pressure of steel pipe, fault displacement, and diameterthickness ratio of steel pipe on the bending of steel pipe [16]. Liu and Wang introduce the nonlinear pipe-soil interaction model into the analysis of lateral global bending of pipelines and investigate the bending characteristics of submarine pipelines with single-arch symmetric initial imperfections under different pipe-soil interaction models [17].…”
Section: Introductionmentioning
confidence: 99%